Fourth Semester Students’ Perspective of Classroom and Distance Learning During Covid-19 Pandemic in Learning Second Language Acquisition - S, K. Dedy Sandiarsa; Suhaili, Muhamad (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This research aimed to evaluate the fourth semester students’ perspective of Distance Learning (DL) compared to Classroom Learning (CL) in learning Second Language Acquisition (SLA) in English Department Program of Universitas Pendidikan Mandalika in academic year 2022/2023. This research was a qualitative research. The subjects of this research were fourth semester students that consisted 67 students who were learnt SLA through DL and CL. An online questionnaire was sent to all of the subjects. After the data have been collected, the researchers  then analyzed the data by theory of Huberman (1994), the Qualitative Data Analysis was done with three steps; Data reduction, Data Display and Conclusion. Based on the analysis data, it was found that the DL students experienced some problems during learning the theory of SLA, the result of questionnaire showed that SLA learning process through DL was not run efficiently than CL. Moreover, the result of questionnaire of CL students showed that CL process gave motivation for self-directed learning and communication with lecturers and their fellow students was easier with CL.